Control de inventarios en la empresa Karlita de la ciudad de Babahoyo - Ramírez Alvarado, Nilo Santiago (2020)
The present case study was carried out at the Karlita company, which is located on Barreiro S / N and June 5 streets in the city of Babahoyo, with the aim of determining the causes and effects that produce inadequate inventory control. Inside the company. The investigation of the work was carried out under the parameters of the line of investigation of the Administrative Management Model, because it focuses on an analysis of everything related to the management that the administrators carry out in relation to inventory control, use will be made analytical and inductive methods which will allow to establish the causes of the existing problem through the application of information gathering instruments such as interviews aimed at company workers. Based on the research carried out, the following results were obtained, among them: the deficiency in the physical control of the inventories is observed, inadequate degree of authority of the managers, lack of signaling of the product sections, poor logistics of merchandise supply to supply the warehouse stocks, lack of adequate supply and demand forecasts, excessive orders to suppliers in certain merchandise.